The anatomy of human rights in Israel : constitutional rhetoric and state practice - Meydani, Assaf (2014)
"Why is there such a large gap between the declarations that countries make about human rights and their imperfect implementation of them? Why do states that have enacted laws and signed treaties about human rights choose to not enforce these laws in daily life? Why have activists failed to achieve the goals of ensuring human rights domestically and internationally? This book examines the issue of human rights in the Israeli domestic arena by analyzing the politics and strategies of defending human rights. To do so, it integrates the tools of social choice theory with a unique institutionalist perspective that looks at both formal and informal, and local and international factors. The book offers an analysis explaining the processes through which Israel is struggling to promote human rights within a specific institutional environment, thus determining the future of Israeli democracy and its attitude toward human rights"--
Introduction -- Institutional theory and social choice studies : understanding the anatomy of human rights -- Between constitutional rhetoric and state practice -- Structural and cultural variables favoring a short-term orientation -- The right to be free from the threat of torture -- The right to equality : gender segregation on Orthodox buses following the Israeli High Court of justice's 2011 ruling on the "segregated lines" -- The right to enjoy a decent lifestyle : the case of the Laron Law : National Insurance Law (Amendment no. 109) of 2008 encouraging the disabled to work -- The human rights commission in Israel that never was -- Property rights : designing the separation fence policy -- The right to human dignity and liberty : the organ transplant law 5768-2008 -- Policy evaluation : analyzingthe reality for human rights.
Includes bibliographical references (pages 273-292) and index.
Keywords: Human rights -- Israel; Human security -- Israel; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Human rights; Human security; Politics and government; Menschenrecht; Menschenrechtspolitik; Menschliche Sicherheit; Israel -- Politics and government; Israel; Israel